Acute Percutaneous Repair of Medial Collateral Ligament With Suture Augmentation in the Multiligamentous Injured Knee Results in Good Stability and Low Rates of Postoperative Stiffness - Kurt Holuba, B.A; Sebastian Rilk, M.D., M.S; Harmen D. Vermeijden, M.D; Robert O'Brien, M.H.S., P.A.-C; Jelle P. van der List, M.D., Ph.D; Gregory S. DiFelice, M.D (Elsevier, 2023)
Purpose: To assess the clinical and patient-reported outcome measures (PROMs) of acute superficial medial collateral ligament (sMCL) repair with suture augmentation (SA) in the setting of a multiligamentous injured knees (MLIKs) at 2-year follow-up. Methods: A retrospective analysis of consecutive patients with MLIK with grade III sMCL injuries who underwent acute (<6 weeks) sMCL repair with SA was conducted. Clinical follow-up was performed at minimum 1-year postoperatively, and PROMs were collected at the latest follow-up (minimum 2 years' postoperatively). Continuous variables were reported in median with interquartile range (IQR). Results: A total of 20 patients (41.4 [28.5-47.9] years of age) with grade III sMCL injury and additional injury to 1 cruciate ligament (KDI-M; n = 13) or bicruciate (KDIII-M; n = 7) were enrolled with a median follow-up of 4.3 (3.6-5.2) years. In total, 90% (n = 18) of patients with MLIK treated with acute sMCL repair and early range of motion rehabilitation protocol demonstrated negative valgus laxity stress testing in 0 and 30° flexion and low reoperation rates (n = 1, 5%) due to stiffness. In addition, good-to-excellent subjective outcomes were reported at final follow-up: median International Knee Documentation Committee 82.2 (78.7-90.8), Lysholm 95.0 (90.0-100.0), modified Cincinnati Score 89.0 (83.3-96.0), Single Assessment Numeric Evaluation 90.0 (83.8-95.0), Forgotten Joint Score 79.2 (62.5-91.7), Tegner 5.0 (IQR 4.0-6.0), and ACL-Return to Sport after Injury Scale 78.3 (IQR 66.7-90.0). Conclusions: In this study, 20 heterogenous patients with MLIKs treated with acute percutaneous sMCL repair with SA had excellent stability, low rates of postoperative stiffness, and good-to-excellent PROMs at short-term follow-up. Level of Evidence: Level IV, therapeutic case series.